The escape from balance sheet recession and the QE trap : a hazardous road for the world economy - Koo, Richard (Wiley, 2014)
Compare global experiences during the balance sheet recession and find out what is needed for a full recovery The Escape from Balance Sheet Recession and the QE Trap details the many hidden dangers remaining as the world slowly recovers from the balance sheet recession of 2008. Author and leading economist Richard Koo explains the unique political and economic pitfalls that stand in the way of recovery from this rare type of recession that was largely overlooked by economists. Koo anticipated the current predicament in the West long before others and issued warnings in his previous books: Bala.